2020
DOI: 10.3389/fphy.2020.568206
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Challenges in Proton Minibeam Radiotherapy: Physics and Biomedical Aspects

Abstract: The concept of spatial fractionation in radiotherapy was developed for better sparing of normal tissue in the entrance channel of radiation. Spatial fractionation utilizing proton minibeam radiotherapy (pMBRT) promises to be advantageous compared to X-ray minibeams due to higher dose conformity at the tumor. Preclinical in vivo experiments conducted with pMBRT in mouse ear models or in rat brains support the prospects, but the research about the radiobiological mechanisms and the search for adequate applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…Proton minibeam radiation therapy is a novel therapeutic approach which, in preclinical experiments, has already shown significant increases in the preservation of normal tissue [ 2 , 36 , 37 ] while providing equivalent or superior tumour control [ 3 ]. The optimal implementation of pMBRT should use magnetically focussed and scanned minibeams as this would allow it to maximise the irradiation efficiency and flexibility, decrease the contamination of secondary particles and yield a better spatial fractionation of the dose [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proton minibeam radiation therapy is a novel therapeutic approach which, in preclinical experiments, has already shown significant increases in the preservation of normal tissue [ 2 , 36 , 37 ] while providing equivalent or superior tumour control [ 3 ]. The optimal implementation of pMBRT should use magnetically focussed and scanned minibeams as this would allow it to maximise the irradiation efficiency and flexibility, decrease the contamination of secondary particles and yield a better spatial fractionation of the dose [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…An approach to overcome these limitations would be the use of magnetically focussed and scanned minibeams for pMBRT. Indeed, recent publications [ 8 , 9 ] suggest that the optimal implementation of pMBRT should use magnetic focussing instead of mechanical collimation for minibeam generation, as it can significantly increase both the irradiation efficiency and flexibility and also improve the degree of spatial fractionation in healthy tissue.…”
Section: Introductionmentioning
confidence: 99%
“…14 Another advantage of beam focusing is that the reduction of the initial beam current resulting from the need to illuminate a collimator surface larger than the holes in it can be avoided. 13 Beam sizes smaller than 0.1 mm and peak-to-valley dose ratios (PVDR) bigger than 10 4 : 1 were already realized for an array of 20 MeV focused proton beams in a skin model study. 5 Small animal studies with deeper located targets are the next step to evaluate the potential of pMBRT for clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Pencil minibeam spot scanning may have the best potential of tissue sparing compared to planar minibeams 8,13 . In the past, results from a human skin model 5 and a study within a mouse ear model 9,11,12 and in the rat brain 10 have shown the potential of pMBRT for reduced side effects compared to a homogeneous irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation